Gene profile in the spleen under massive partial hepatectomy using complementary DNA microarray and pathway analysis. Issue 8 (August 2014) - Arakawa, Yusuke; Shimada, Mitsuo; Utsunomiya, Tohru; Imura, Satoru; Morine, Yuji; Ikemoto, Tetsuya; Mori, Hiroki; Kanamoto, Mami; Iwahashi, Shuichi; Saito, Yu; Takasu, Chie
Abstract Background and Aim In general, the spleen is one of the abdominal organs connected by the portal system, and a splenectomy improves hepatic functions in the settings of partial hepatectomy (Hx) for portal hypertensive cases or living donor liver transplantation with excessive portal vein flow. Those precise mechanisms remain still unclear; therefore, we investigated the DNA expression profile in the spleen after 90% Hx in rats using complementary DNA microarray and pathway analysis. Methods Messenger RNAs (mRNAs) were prepared from three rat spleens at each time point (0, 3, and 6 h after 90% Hx). Using the gene chip, mRNA was hybridized to Affymetrix GeneChip Rat Genome 230 2.0 Array (Affymetrix®) and pathway analysis was done with Ingenuity Pathway Analysis (IPA®). Results We determined the 3‐h or 6‐h/0‐h ratio to assess the influence of Hx, and cut‐off values were set at more than 2.0‐fold or less than 1/2 (0.5)‐fold. Chemokine activity‐related genes including Cxcl1 (GRO1) and Cxcl2 (MIP‐2) related pathway were upregulated in the spleen. Also, immediate early response genes including early growth response‐1 (EGR1), FBJ murine osteosarcoma (FOS) and activating transcription factor 3 (ATF3) related pathway were upregulated in the spleen. Conclusions We concluded that in the spleen the expression of numerous inflammatory‐related genes would occur after 90% Hx. The spleen could take a harmful role and provide a negative impact during post Hx phase due to the induction of chemokine and transcription factors including GRO1 and EGR1.